Karya Al-Muwatha di Mata Muhammad Thahir Ibn Asyur - Rizki Putriani (Al-Fath, 2022)
Abstrack Paper aims to find out the criticism of Ibn Ashur on the book of al Muwatta' Imam Malik starting from discussing the biography of Ibn Ashur, the opinion of scholars about Ibn Ashur, the views of hadith scholars about the book of AThis l-Muwatha, and the last one discusses Ibn Ashur's views on the book of Al-Muwatha. This research is purely library research using the book Kasyful Mughoti as the main reference along with other books related to 'Ulum al-Hadis' as supporting data. The type of research is descriptive qualitative research using various approaches to hadith science. The results showed that according to Ibn Ashur there was no one among the people who had a hadith that was more authentic than Malik bin Anas Malik. According to Ibn Assyria in the book Al Muwatha' Ibn Malik made a comprehensive chapter in it at the end he mentioned what was not included in the special chapter. Al-Muwatta' is a book of Hadith revealed from the Prophet with a chain of narrators from Malik to the Rasullah. Keywords: Al-Muwatha, In the Eyes of, Muhammad Thahir Ibn Ashur